Spider Web-Inspired Graphene Skeleton-Based High Thermal Conductivity Phase Change Nanocomposites for Battery Thermal Management - Lin, Ying; Kang, Qi; Wei, Han; Bao, Hua; Jiang, Pingkai; Mai, Yiu‑Wing; Huang, Xingyi (Nano-Micro Letters, 2021)
Phase change materials (PCMs) can be used for efficient thermal energy harvesting, which has great potential for cost-effective thermal management and energy storage. However, the low intrinsic thermal conductivity of polymeric PCMs is a bottleneck for fast and efficient heat harvesting. Simultaneously, it is also a challenge to achieve a high thermal conductivity for phase change nanocomposites at low filler loading. Although constructing a three-dimensional (3D) thermally conductive network within PCMs can address these problems, the anisotropy of the 3D framework usually leads to poor thermal conductivity in the direction perpendicular to the alignment of fillers. Inspired by the interlaced structure of spider webs in nature, this study reports a new strategy for fabricating highly thermally conductive phase change composites (sw-GS/PW) with a 3D spider web (sw)-like structured graphene skeleton (GS) by hydrothermal reaction, radial freeze-casting and vacuum impregnation in paraffin wax (PW). The results show that the sw-GS hardly affected the phase transformation behavior of PW at low loading. Especially, sw-GS/PW exhibits both high cross-plane and in-plane thermal conductivity enhancements of ~ 1260% and ~ 840%, respectively, at an ultra-low filler loading of 2.25 vol.%. The thermal infrared results also demonstrate that sw-GS/PW possessed promising applications in battery thermal management. Highlights: 1 A three-dimensional spider web-inspired structured graphene skeleton is constructed. 2 The spider web-like skeleton endows paraffin wax with a significantly high longitudinal and transverse thermal conductivity enhancement of ~1260% and ~840%, respectively, at 2.25 vol% skeleton. 3 The resultant composites exhibit outstanding performance on the thermal management of Li-ion batteries.